2014
DOI: 10.1097/jcp.0000000000000049
|View full text |Cite
|
Sign up to set email alerts
|

Early Improvement in Depressive Symptoms With Desvenlafaxine 50 mg/d as a Predictor of Treatment Success in Patients With Major Depressive Disorder

Abstract: Clinical observations of patients' early response to desvenlafaxine 50 mg/d may have clinical value in predicting treatment success and guiding patient management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 34 publications
2
21
0
1
Order By: Relevance
“…Symptomatic improvement during the first few weeks of treatment has been shown to predict later response or remission with some antidepressants (Szegedi et al, 2003(Szegedi et al, , 2009Kok et al, 2009;Soares et al, 2014) and may also be predictive of improvements in functioning. However, few randomized controlled trials have evaluated the effects of antidepressant treatment on functional outcomes in patients with MDD (Kocsis et al, 2002;Szegedi et al, 2003;Trivedi et al, 2010;Dunlop et al, 2011;Oakes et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Symptomatic improvement during the first few weeks of treatment has been shown to predict later response or remission with some antidepressants (Szegedi et al, 2003(Szegedi et al, , 2009Kok et al, 2009;Soares et al, 2014) and may also be predictive of improvements in functioning. However, few randomized controlled trials have evaluated the effects of antidepressant treatment on functional outcomes in patients with MDD (Kocsis et al, 2002;Szegedi et al, 2003;Trivedi et al, 2010;Dunlop et al, 2011;Oakes et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Early improvement was usually defined as at least 20 % reduction in HAM-D or MADRS (n = 11 studies). Two studies also examined optimum definitions of early improvement using receiver operating characteristic analysis [16,17]. For early improvement at 2 weeks, PPVs were 26-84 %, while NPVs were 35-92 %.…”
Section: Predictive Value Of Early Improvementmentioning
confidence: 99%
“…[18][19][20][21][22][23][24] A series of analyses have been conducted to examine the predictive value of early improvement of depressive symptoms on other treatment outcomes using data from placebo-controlled trials of desvenlafaxine for the treatment of MDD. 17,25,26 In addition to confirming an effect of early symptom improvement on the probability of achieving response and remission from depression, 17 analyses have demonstrated that early depressive symptom improvement could also predict later functional outcomes in MDD patients treated with desvenlafaxine 50 mg or placebo. 25,26 Week-2 improvements (depressive symptoms in one study 26 and functional improvement in a pooled analysis 25 ) were significant predictors of functional outcomes (Sheehan Disability Scale 27 [SDS] score, functional response, or functional remission) at study end (week 8 or week 12).…”
Section: Introductionmentioning
confidence: 95%
“…16 Results of analyses show that improvement in depression symptoms within 2-4 weeks of starting an antidepressant predicts response and remission 7 and, importantly, that failure to show early improvement predicts poor treatment outcomes. 17 The predictive value of lack of early improvement (i.e., negative predictive value (NPV)) has been demonstrated across antidepressant drug classes in patients treated with tricyclic antidepressants, selective serotonin reuptake inhibitors, serotoninnorepinephrine reuptake inhibitors, and new-generation antidepressants. 7 Thus, adjustments to medication regimen, starting with dose optimization, should be considered as early as 2 weeks after initiation of treatment.…”
Section: Introductionmentioning
confidence: 99%